VEIL OR EVIL? SPOTLIGHTING WOMEN PORTRAYAL THROUGH SEMIOTICS ANALYSIS - Fata, Ika Apriani (State Institute of Islamic Studies Salatiga, 2018)
The phenomenon of woman and man portrayal has been discussed worldwide. Many viewpoints such as media, politics, health, cultural studies, gender concerned on this topic. However, only a few of them was trying to seek out the language features attributed for women representation. Accordingly, to fill in this gap, this research aims at describing semiotic sign analysis of woman portrayal in media. A number of four data of Serambi Indonesia column were analyzed based on two signification semiotics interpretations of Barthes (1967). The result eventually revealed that the language features attributed for women in the newspaper are woman as animal, as properties, as trigger of sins, as peaceful guard, those are considered as terms of denotative signification meaning. Meanwhile, the connotative meaning divided into two understandings; veil and evil, introducing positive and negative representation towards women. Finally, it is expected that for further studies involve systemic functional linguistics or corpus linguistics towards other discourses as media to further develop the conclusions drawn fromthis present study.Keywords: Woman, Aceh, semiotics, portrayal, signification.